SINKRETISME DALAM TRADISI ZIARAH KERAMAT DI BANTEN - Safitri, Gita (UI Scholars Hub, 2025)
This review will analyze a book entitled Sinkretisme dalam Tradisi Ziarah Keramat di Banten by Helmy Faizi Bahrul Ulumi which reflects the richness of local culture in the Banten region, especially on relic sites that become pilgrimage destinations for the community. The popularity of the sacredness of sacred places is an attraction that not only has spiritual value but also sacredness becomes an important point as an inherent local belief. This review will evaluate the depiction of syncretism in pilgrimage practices to the construction of its meaning.